Flashcard Augmented Reality: Sebuah Media Menstimulasi Kemampuan Berpikir Simbolik Anak Usia Dini - Ayu Nuri Azizati, Intan; Nurhayati Adhani, Dwi (Nak-Kanak: Journal of Child Research, 2024)
This study was conducted to investigate the effectiveness of using augmented reality flashcards in stimulating the cognitive development of 4-5-year-old children at TK Bina Ria, particularly in symbolic thinking abilities. The research employed a quantitative experimental model with a Pre-Experimental design, specifically the One Group Pretest design. The study population comprised children aged 4-5 years attending TK Bina Ria, with a sample size of 30 children selected using nonprobability sampling techniques. Data collection methods included tests, observations, and documentation. The research findings indicated that the use of augmented reality flashcards stimulates cognitive development in symbolic thinking abilities. Flashcards with relevant symbols, words, numbers, and pictures assist children in visually grouping, collecting, and organizing objects. This aids them in recognizing logical relationships, categorizing objects, and concretizing ideas. The study also noted that the preoperational stage, which involves various cognitive abilities relevant to children's symbolic thinking, aligns with Piaget's theory. Upon reviewing the results of the t-test, a Sig value (2-tailed) of 0.000 < 0.05 was obtained, indicating a significant difference between pretest and posttest values. This significant difference is evident in the average scores before and after the implementation of the media, with a pretest average of 12.33 and a posttest average of 28.67. This study contributes to providing one method of stimulating children's symbolic thinking abilities through the use of augmented reality flashcards